Conformational preferences and phase behavior of intrinsically disordered low complexity sequences: insights from multiscale simulations. (June 2019) - Ruff, Kiersten M; Pappu, Rohit V; Holehouse, Alex S
Highlights: Low complexity (LC) sequences are prominent in eukaryotic proteomes. LC sequences are composed of a parsimonious subset of the naturally occurring amino acids. A significant fraction of LC sequences are intrinsically disordered. Theory and computation can be deployed to uncover the conformational properties and phase behaviors of disordered LC sequences. Such methods show that conformational properties and phase behavior are governed by compositional biases and sequence patterns. Abstract : While many proteins and protein regions utilize a complex repertoire of amino acids to achieve their biological function, a subset of protein sequences are enriched in a reduced set of amino acids. These so-called low complexity (LC) sequences, specifically intrinsically disordered variants of LC sequences, have been the focus of recent investigations owing to their roles in a range of biological functions, specifically phase separation. Computational studies of LC sequences have provided rich insights into their behavior both as individual proteins in dilute solutions and as the drivers and modulators of higher-order assemblies. Here, we review how simulations performed across distinct resolutions have provided different types of insights into the biological role of LC sequences.